The plot and the pendulum - McKinlay, Jenn (McKinlay, Jenn. Library lover's mysteries, 2022)
"Halloween is approaching in Briar Creek, and things get spooky when a skeleton is found and connected to a decades-old cold case. Library director Lindsey Norris is happy to learn the Briar Creek Public Library is the beneficiary of the Dorchester family's vast book collection. However, when Lindsey and the library staff arrive at the old Victorian estate to gather the books, things take a sinister turn. One of the bookcases reveals a secret passage, leading to a room where a skeleton is found, clutching an old copy of The Collected Works of Edgar Allan Poe. Lindsey does a quick check of missing persons, using the distinctive eighties-era clothing worn by the deceased to determine a time frame, and discovers that Briar Creek has an unsolved missing person's case from 1989. A runaway bride went missing just weeks after her wedding. No suspects were ever arrested and the cold case remains unsolved. Lindsey and the crafternoon crew decide that justice is overdue and set about solving the old murder mystery, using some novel ideas to crack the case"--